A direct test of the endogeneity of money: implications for Gulf Cooperation Council (GCC) countries - Bedri Kamil Onur Tas; Selahattin Togay (Turkish Economic Association, 2010)
This paper contributes to the ongoing discussion about the endogeneity of money supply by empirically investigating the GCC countries. We propose and implement a direct test of money supply endogeneity that depends on econometric specification of exogeneity. To be able to make comparisons with previous studies in the literature, we also conducted Granger Causality tests to analyze the causality relationship between bank credit and money supply. Both of the empirical studies provide empirical evidence for the endogeneity of money supply in GCC countries. The results of the paper have many significant monetary policy implications for the upcoming monetary unification of the GCC countries.
Keywords: 330; Geldmenge; Bankgeschäft; Geldpolitik; Arabische Golf-Staaten